CompTIA A+ complete study guide : Core 1 Exam 220-1101 and Core 2 Exam 220-1102 - Docter, Quentin; Buhagiar, Jon (Sybex, 2022)
The Fifth Edition of the CompTIA A+ Complete Study Guide: Core 1 Exam 220-1101 and Core 2 Exam 220-1102 offers accessible and essential test preparation material for the popular A+ certification. Providing full coverage of all A+ exam objectives and competencies covered on the latest Core 1 and Core 2 exams, the book ensures you'll have the skills and knowledge to confidently succeed on the test and in the field as a new or early-career computer technician. The book presents material on mobile devices, hardware, networking, virtualization and cloud computing, network, hardware, and software troubleshooting, operating systems, security, and operational procedures. Comprehensive discussions of all areas covered by the exams will give you a head start as you begin your career as a computer technician. This new edition also offers: Accessible and easy-to-follow organization perfect to prepare you for one of the most popular certification exams on the market today Opportunities to practice skills that are in extraordinary demand in the IT industry Access to the Sybex online test bank, with chapter review questions, full-length practice exams, hundreds of electronic flashcards, and a glossary of key terms Perfect for anyone prepping for the Core 1 and Core 2 A+ exams, CompTIA A+ Complete Study Guide: Core 1 Exam 220-1101 and Core 2 Exam 220-1102 is a must-have resource for new and early-career computer technicians seeking to improve their skills and increase their efficacy in the field.